The Artisanal Cheese Factory in the Context of the Araucanía Region – Chile - Angulo , Julio Tereucán; Barría , Luis Torralbo; Ferrari, Claudia Barchiesi; Aravena, Susana Valenzuela; González, Silvana Catrilaf; Chepo, Manuel Mora (International Journal of Membrane Science and Technology, 2023)
Traditional artisanal cheeses are known in Chile and Argentina as country cheeses, or in some other places as farm cheeses or farmhouse cheeses. All these terms are used to refer to cheeses made in small workshops or cheese factories, where the process is carried out by hand by the same members of the family and with a minimum presence of employees. A distinctive feature of cheese production is that the production processes have incorporated elements of the culture and environment in which the activity takes place. the purposes of this article referred to characterize the artisanal cheese factory and its producers in the context of the Araucanía Region in Chile. The region of La Araucanía is located in Chile, between the regions of Bío Bío and Los Ríos. Its area is 31,842 km² and its regional capital is the commune of Temuco. The type of study is quantitative of a transitional-descriptive type in 19 communes and 137 cheese producers of the provinces of Malleco and Cautín in the region of La Araucanía, territories where the cheese producers that are part of the sample are located. The characteristics of the producers, cheese factories and processes associated with the production of cheese, account for a cheese reality that has a set of potentialities and complexities necessary to consider not as problems of the artisanal cheese factory, but as realities and baselines on which it works and it is necessary to continue working in post of its empowerment and its value as part of the agri-food production system in the region of La Araucanía-Chile.